1991
DOI: 10.1080/01904169109364276
|View full text |Cite
|
Sign up to set email alerts
|

Calcium uptake and concentration in bell pepper plants as influenced by nitrogen form and stages of development

Abstract: Calcium uptake by bell pepper (Capsicum annuum L. cv. 'California Wonder') varied by stage of plant development and N form supplied (NQ 3 -NH 4 + ratios: 1:0, 3:1, 1:1, 1:3, and 0:1) in a hydroponic study. Uptake of Ca ++ was highest at bloom and during fruit expansion, making the fruit development stage the highest demand period. Calcium uptake declined with each increasing increment of NH 4 + relative to NO 3 -supplied, although fruit yield was not significantly reduced until the ratio of NH 4 + to NO 3 -exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 9 publications
8
20
0
Order By: Relevance
“…Bar-Tal et al (2001) observed that decreasing the NO 3 − /NH 4 + ratio sharply decreased the uptake of cations by pepper. That response was also reported by Marti and Mills (1991), each increment in NH 4 + decreasing the uptake of K + . However, we observed that this effect cannot be directly attributed to a dilution effect derived from the greater biomass at e[CO 2 ] under salinity stress.…”
Section: Nosupporting
confidence: 68%
“…Bar-Tal et al (2001) observed that decreasing the NO 3 − /NH 4 + ratio sharply decreased the uptake of cations by pepper. That response was also reported by Marti and Mills (1991), each increment in NH 4 + decreasing the uptake of K + . However, we observed that this effect cannot be directly attributed to a dilution effect derived from the greater biomass at e[CO 2 ] under salinity stress.…”
Section: Nosupporting
confidence: 68%
“…Nearly all fertigation in the region is done using premixed liquid fertilizers containing Ca or K with nitrate as the N source. Growers generally avoid ammonium forms of N due to the association of ammonium with increased BER in bell pepper (Marti and Mills, 1991).…”
mentioning
confidence: 99%
“…In pepper, increased irrigation N concentrations and NH 4 + :NO 3 -ratios increased the incidence of blossom-end rot (Bar-Tal et al, 2001a;Marti and Mills, 1991). Increased NH 4 + levels also increased the occurrence of blossom-end rot in tomato Wojciechowski et al, 1969).…”
Section: Discussionmentioning
confidence: 89%
“…Increased NH 4 + supply, or NH 4 :NO 3 ratio, were demonstrated to reduce cation, (especially K, Mg, and Ca) uptake and levels in the organs of several plants, probably as a result of increased NH 4 + uptake through a charge balance mechanism in ion uptake (Ganmore-Neumann and Kafkafi, 1980;Marti and Mills, 1991;Bar-Tal et al, 2001b).…”
Section: Discussionmentioning
confidence: 97%